Development and validation of a new stability indicating RP-UPLC method for the simultaneous estimation of Tenofovir Alafenamide, Emtricitabine and Bictegravir in presence of internal standard (Acyclovir) - Asia; Revu Baby Nalanda (The Bioscan, 2025)
A new stability indicating RP-UPLC method has been proposed for the simultaneous estimation of Tenofovir Alafenamide, Emtricitabine and Bictegravir in presence of an internal standard, Acyclovir using Waters ACQUITY UPLC system with PDA detector and Hibar C18 (100 x 2.1 mm, 1.8) column. Mobile phase consisting of 0.01M Ammonium acetate and Acetonitrile (70:30, v/v) was used with flow rate 0.3 ml/min (Detection wavelength: 260 nm) (Injection volume: 1.0 L) (Column temperature: 30°C) with run time 6 mins. The method was linear over the concentration range 2.5-15 µg/ml, 20-120 µg/ml and 5-30 µg/ml for Tenofovir Alafenamide, Emtricitabine and Bictegravir respectively. Forced degradation studies were performed and the method was validated as per ICH guidelines.